AI’s Democratic Challenge: Reflections on the Law and Political Economy of Artificial Intelligence - Zumbansen, Peer (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2024)
Artificial intelligence (AI) is variably identified as “job killer,” as “inhuman,” as “unpredictable” and “ungovernable,” but also as the greatest technological innovation in generations. Lawyers struggle with AI across a host of legal fields, including consumer protection, constitutional, employment, administrative, criminal, and refugee law. While AI is commonly discussed as a question of technological progress, its core challenge is a political one. As AI is used as a tool to review employment recruitment files, assess loan, mortgage, or visa applications and to collect and process data of “suspicious” actors, it deepens existing inequalities and socio-economic vulnerability. Given the rapidly expanding reach of AI into most facets of social, economic, and political life, AI shapes people’s access to democratic life in an unprecedented and increasingly precarious manner. Efforts to address its promises and perils through a lens of “AI ethics” can therefore hardly capture the scope of challenges which arise from AI. Seen from a historical perspective, then, AI accentuates and reinforces trends of inequality, social alienation, and political volatility which began long before AI’s implications in society’s daily lives.